Acute Groin Pain Syndrome Due to Internal Obturator Muscle Injury in a Professional Football Player - Bisciotti, Gian N.; Corsini, Alessandro; Cena, Emanule; Bisciotti, Andrea N.; Bisciotti, Alessandro L.; Belli, Andrea; Volpi, Piero (Joints, 2019)
Traumatic groin pain syndrome is the result of an acute trauma, usually an indirect muscle injury (i.e., an overstretching of the muscle fibers). The most affected muscles in traumatic groin pain syndrome are rectus abdominis, adductors, and iliopsoas. The internal obturator muscle lesion is very rare. The internal obturator muscle externally rotates the thigh and contributes to the stabilization of the hip joint and its indirect injury may cause the onset of traumatic groin pain syndrome. This case report describes a rare indirect injury of internal obturator in a 29-year-old professional male soccer player.
Keywords: internal obturator; indirect lesion; groin pain syndrome; treatment